Grecoli Candy from Grape and Broccoli to Boost the Body's Immune System in the Middle of the COVID-19 Pandemic - Fadhil Fathurochman; Hartatiek Hartatiek; Nadya Eka Agustin Ermalita; Lintang Miftahul Rizki; Norhayati Ahmad (Universitas Negeri Malang, 2022)
Grapes and broccoli have been scientifically proven to have high antioxidant content to increase the body's immune power compared to other fruits or vegetables. An immunomodulator is a compound that can regulate the activity and function of the immune system. The purpose of this study was to find out how to improve the body's immune system amid the COVID-19 pandemic and also to find out how to make food practically consumed to help increase the body's immunity during the COVID-19 pandemic. In this study, grapes and broccoli were extracted and then boiled at a temperature of ±85–100℃, then mixed with several ingredients, including sucrose, glucose, citric acid, gelatin, and flavourings. The antioxidant test was carried out using the Ferric Reducing Antioxidant Power (FRAP) method. After obtaining the antioxidant value, a spectrophotometric test was carried out to determine the maximum wavelength and absorbance value obtained. For the first sample, the results were 22.88 mmAAE/mL extract. In contrast, the second sample obtained results of 25.01mmAAE/mL extract.DOI: 10.17977/um024v7i12022p046